2016
DOI: 10.1016/j.ssci.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Crowd sourcing disaster management: The complex nature of Twitter usage in Padang Indonesia

Abstract: -IntroductionGovernment officials, first responders and the general public are increasingly looking to social media as a critical communication and monitoring tool for disaster management. Due to widespread press coverage and ease of data collection, Twitter in particular is viewed as a critical communication media for disaster management. Key advantages include crowd-sourcing, speed, and the ability to access from mobile devices. Key potential disadvantages include bias in user base; inaccurate, false, and ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(102 citation statements)
references
References 47 publications
1
94
0
7
Order By: Relevance
“…The current system adds a new dimension to social media, where it can be used as a tool for public help. Most of the prior research Huang and Xiao 2015;Carley et al 2016) on uses of social media has mainly concentrated on either evaluating the fitness of social media as a disaster management tool, or detecting tweets related to disasters to warn users about disasters. Some others researchers (Hara 2015) have studied the behavior of Twitter users during disasters.…”
Section: Discussionmentioning
confidence: 99%
“…The current system adds a new dimension to social media, where it can be used as a tool for public help. Most of the prior research Huang and Xiao 2015;Carley et al 2016) on uses of social media has mainly concentrated on either evaluating the fitness of social media as a disaster management tool, or detecting tweets related to disasters to warn users about disasters. Some others researchers (Hara 2015) have studied the behavior of Twitter users during disasters.…”
Section: Discussionmentioning
confidence: 99%
“…Despite, the high prevalence of social media usage during the event, effective response for disaster relief was found to be relatively low [32]. Social media and up to date communication technologies maybe regarded as the fastest point of reference in times of crisis, but the vast information received without restriction via multiple databases exaggerate the difficulty of effective and accurate response to be provided for the victims [33][34]. Another study during the Great East Japan earthquake on 2011 in other hand showed that the use of mobile phones, laptops and landline phones usage were rated poor to moderate satisfactory level during disaster relief [35].…”
Section: 22fixed Mobile Network and Internet-based Communicationmentioning
confidence: 99%
“…Following this, during each mass casualty incidents, responders in hospitals in Malaysia utilize this mode of communication to complement the GIRN services. The only concern with the use of this mode of communication is the guarantee of security and confidentiality [33,21].…”
Section: N Juliana Et Al J Fundam Appl Sci 2017 9(4s) 890-904 896mentioning
confidence: 99%
“…Twitter has gained more recognition as a tool that is able to assist in the disaster management process (Carley et al, ; Landwehr, Wei, Kowalchuck, & Carley, ; Spence, Lachlan, Lin, & del Greco, ), given that its use has strong potential to increase disaster communication efficiency. Aside from being a central information and alert system, Twitter also provides a platform for the narratives of disaster victims, which is useful when it comes to humanitarian assistance and support (David, Ong, & Legara, ).…”
Section: Disaster Managementmentioning
confidence: 99%